2011
DOI: 10.2807/ese.16.42.19993-en
|View full text |Cite
|
Sign up to set email alerts
|

Autochthonous Plasmodium vivax malaria in Greece, 2011

Abstract: Between May and September 2011, twenty cases of Plasmodium vivax infection were reported in Greek citizens without reported travel history. The vast majority of those cases were confined to a delimited agricultural area of Evrotas, Lakonia. Conditions favouring locally acquired transmission of malaria, including the presence of competent vectors and migrants from endemic countries exist in Greece, underscoring the need for the development of an integrated preparedness and response plan for malaria prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(22 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…9,17,18 The first report was a Romanian worker in the area of Skala who returned to his home country after the febrile illness, 17 and in the following months further cases and a much bigger cluster occurred. 9,18 As a result the WHO was notified again and an enhanced surveillance system was implemented, 9 since Greece is on the southern border of Europe and has been handling an increasing number of immigrants coming to the country each year -refugees from Asian countries that are malaria-endemic (Afghanistan and Pakistan) according to the WHO. [19][20][21] In conclusion, we present the first local cluster of autochthonous cases of malaria due to P. vivax in the area of Laconia over the last four decades.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,17,18 The first report was a Romanian worker in the area of Skala who returned to his home country after the febrile illness, 17 and in the following months further cases and a much bigger cluster occurred. 9,18 As a result the WHO was notified again and an enhanced surveillance system was implemented, 9 since Greece is on the southern border of Europe and has been handling an increasing number of immigrants coming to the country each year -refugees from Asian countries that are malaria-endemic (Afghanistan and Pakistan) according to the WHO. [19][20][21] In conclusion, we present the first local cluster of autochthonous cases of malaria due to P. vivax in the area of Laconia over the last four decades.…”
Section: Discussionmentioning
confidence: 99%
“…No other case was reported in 2010, but in 2011 a new cluster of malaria cases occurred and another intervention program was implemented. 9…”
Section: Clinical and Epidemiological Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This theory would predict, for example, that there are places in malaria elimination countries where malaria would be highly explosive if it were introduced today. Indeed, there have been a few highly explosive epidemics in malaria-free countries, the most recent occurring in Greece [108]. The aggregated data describing importations, however, demonstrate that these large outbreaks are the exception to the rule.…”
Section: Is Elimination Stable Because Importation Is Not Effective At Rekindling Transmission?mentioning
confidence: 98%
“…As a result, a seroepidemiological study conducted in 1997-1999 at the same place showed that 0,8% of the individuals tested were seropositive Kampen, et al [2]. It was in 2009 that autochthonous cases commenced re-emerging in Greece, leading to the formation of specific malarious hot spots (such as Evrotas region) in the country Danis et al [3].…”
Section: Short Communicationmentioning
confidence: 99%